Cellular metabolic profiling of CrFK cells infected with feline infectious peritonitis virus using phenotype microarrays - Ng, Shing Wei; Selvarajah, Gayathri Thevi; Cheah, Yoke Kqueen; Mustaffa Kamal, Farina; Omar, Abdul Rahman (MDPI, 2020)
Feline infectious peritonitis (FIP) is a fatal feline immune-mediated disease caused by feline infectious peritonitis virus (FIPV). Little is known about the biological pathways associated in FIP pathogenesis. This is the first study aiming to determine the phenotypic characteristics on the cellular level in relation to specific metabolic pathways of importance to FIP pathogenesis. Methods: The internalization of type II FIPV WSU 79-1146 in Crandell-Rees Feline Kidney (CrFK) cells was visualized using a fluorescence microscope, and optimization prior to phenotype microarray (PM) study was performed. Then, four types of Biolog Phenotype MicroArray™ plates (PM-M1 to PM-M4) precoated with different carbon and nitrogen sources were used to determine the metabolic profiles in FIPV-infected cells. Results: The utilization of palatinose was significantly low in FIPV-infected cells; however, there were significant increases in utilizing melibionic acid, L-glutamine, L-glutamic acid and alanyl-glutamine (Ala-Gln) compared to non-infected cells. Conclusion: This study has provided the first insights into the metabolic profiling of a feline coronavirus infection in vitro using PMs and deduced that glutamine metabolism is one of the essential metabolic pathways for FIPV infection and replication. Further studies are necessary to develop strategies to target the glutamine metabolic pathway in FIPV infection.